Large-scale carbon framework microbelts anchoring ultrafine SnO2 nanoparticles with enhanced lithium storage properties. (20th February 2019) - Wang, Qishang; Xu, Junqi; Shen, Guangyue; Guo, Yaqing; Zhao, Xun; Xia, Yanjie; Sun, Haibin; Hou, Peiyou; Xie, Wenhe; Xu, Xijin
Abstract: Varieties of nanostructured SnO2 have been widely investigated as promising anode material for next generation lithium-ion batteries (LIBs). However, traditional nanostructures suffer from re-agglomeration and excessive side reactions, which lead to low coulombic efficiency, poor rate performance and dramatic capacity decay. Here we develop an easy and robust strategy to fabricate carbon framework microbelts anchoring ultrafine SnO2 nanoparticles (U-SnO2 NPs@ CF-MBs), which takes advantage of the synergistic effect between high conductivity of large-size carbon framework and high activity of ultrafine SnO2 nanoparticles. The as-fabricated U-SnO2 NPs@C-BsF composite deliver high capacity of 925 mAh g −1 after 250 cycles at current density of 200 mA g −1, high rate capacity of 464 mAh g −1 at a high current density of 5000 mA g −1 and long cycle performance of 788 mAh g −1 after 1000 cycles at current density of 1500 mA g −1 in half cells. When applied in a full cell by coupling with a LiCoO2 cathode, the fabricated U-SnO2 NPs@ CF-MBs composite full cells keep a high capacity of 510 mAh g −1 after 80 cycles. Notably, the electrode exhibit two platforms located at 3.3 and 2.6 V, which indicate that the conversion between SnO2 and Sn is also highly reversible in full cells. The excellent lithium storage of large-scale U-SnO2 NPs@ CF-MBs ensures its great promise for commercial utilization in the future LIBs.